Co-Production of Disability and Race: Reading for Disability in Black Prison Writings - Bunton, Zoe (Undergraduate Research Journal for the Humanities, 2017)
Disability studies scholars have called for a critical refocusing of disability as not only an identity that intersects with race but also as an identity rooted in racialization. By reading the prison writings of Mumia Abu-Jamal across the grain as a disability text, the co-constitution of Blackness, disability, and criminalization is evident in not just disability studies scholarship, but also the lived experiences of Black, criminalized authors. By applying critical theoretical lenses of race and disability to works like Live from Death Row, one can better identify how the disenfranchisement of Black people is purported to be natural in American culture.